STANDARD AGREEMENTS IN BUSINESS LAW: STUDIES IN CREDIT IN THE BANKING WORLD - Sisca Ferawati Burhanuddin (Fox Justi : Jurnal Ilmu Hukum, 2023)
The standard agreement is one of the instruments that is often used in business law practices, including in the banking sector, especially in credit. This study aims to analyze the use of Standard Agreements in credit in banking and their effectiveness in resolving disputes in the banking sector. This study uses a normative juridical research method using analytical descriptive. The results of the study show that the use of Standard Agreements in credit in banking is commonly practiced and regulated in laws and regulations adapted to Law Number 8 of 1999 concerning consumer protection. However, the implementation of the Standard Agreement still creates various problems such as injustice for consumers and limitations in resolving disputes, this can be seen from the many unfair clauses that tend to harm consumers. This research also shows that the effectiveness of the Standard Agreement in resolving disputes in the banking sector from the bank is generally carried out in the form of preventive legal protection (preventing problems from occurring and repressive forms of legal protection (resolving problems) while for customers or consumers guided by Article 19 paragraphs 1 and 2 UUPK.